Temperature programmed analysis of hydrogenation and dehydrogenation of magnesium (Mg), nickel (Ni) and aluminum (Al) containing mixed oxides - Salam, M.A. (Institution of Chemical Engineers, 2017)
Hydrotalcite derived magnesium (Mg), nickel (Ni), and aluminum (Al) containing a mixed oxide of Mg0.5Ni0.25Al0.25O1.13has been synthesized using co-precipitation method. Hydrogenation and dehydrogenation of Mg0.5Ni0.25Al0.25O1.13mixed oxide has been studied using conventional temperature programmed reduction (TPR) and temperature programmed desorption (TPD) method. ICP-MS analysis ensured the composition of metals in a solid solution of mixed oxides. Surface composition was confirmed via EDX analysis. Different oxide, spinel phases were predicted by the X-ray diffraction (XRD) and FT-IR analyses. Temperature-programmed reduction/desorption analyses showed remarkable hydrogenation and dehydrogenation at near ambient conditions. Reduced mixed oxides showed significant hydrogenation at a temperature range of 0–180 °C. X-ray diffractogram and FTIR spectroscopy predicted the hydrogenated phases of MgH2and Mg2NiH4as a stable product of hydrogenation. The analyses correspond the physical and chemical adsorption in whole hydrogenation process of Mg0.5Ni0.25Al0.25O1.13mixed oxides. The activation energy of dehydrogenation is 60 kJ/mol which indicate the formation of reversible hydride phases of MgH2and Mg2NiH4. © 2016